Properties of Kenaf Fibre Filled with Natural Rubber/Thermoplastic Polyurethane Composites - Nur Amirah Ayuni, Jamaludin; Nurjannah, Salim; Nurul Huda, Abu Bakar; Rasidi, Roslan (Springer Nature Singapore, 2024)
Due to their advantages over conventional reinforcement materials, natural fibres have recently attracted the attention of scientists and engineers, and the construction of natural fibre composites has been a topic of interest for several years. The use of natural fibres has enabled the creation of composites that are lighter and less expensive than those presently on the market, such as fiberglass-reinforced polymer composites. This study presents the results of an investigation into the effects of alkaline treatment with sodium hydroxide (NaOH) on the properties of kenaf-filled natural rubber (NR) and thermoplastic polyurethane (TPU) composites. The treated kenaf fiber, TPU, and NR were mixed using a single-screw extruder machine. Three sample preparation ratios were prepared: sample 1 (TPU:200 g), sample 2 (TPU:200 g, NR:10 g), and sample 3 (kenaf:10 g, TPU:200 g, NR:10 g). The samples produced were subjected to tensile and impact tests to determine the stress–strain curve for the percentage of elongation and tensile stress values. Sample 1 was found to have the highest Young's modulus, followed by sample 2. In conclusion, adding natural rubber to kenaf/TPU composites improved their properties of the composites produced.